Optimalisasi Peran Dan Fungsi Wali Kelas Dalam Manajemen Peserta Didik Di Sekola - Ridwan Ali; Ali Imron; Sunarni Sunarni (Proceedings Series of Educational Studies, 2023)
Abstract: The frequency of interaction between homeroom teachers and students and parents/guardians aswell as the level of homeroom involvement in overcoming student problems and providingappropriate solutions are important factors in student management in schools. The resul ts of theliterature review show that frequent and positive interactions between homeroom teachers andstudents and parents/guardians can increase learning motivation, parental participation ineducation, and reduce deviant behavior. However, overly frequent and excessive interactions canhave the opposite effect, such as reducing students' confidence and increasing anxiety. Homeroomteachers also have an important role in overcoming student problems and providing appropriatesolutions to address various student problems. However, the level of homeroom involvement canvary depending on factors such as experience, motivation, and ability. Therefore, support andtraining are needed for homeroom teachers to improve their skills and involvement in helpingstudents overcome problems and achieve better results. It is important to find the right balance inthe frequency of interactions and ensure that those interactions are of good quality and positive tosupport the achievement of student learning goals.Keywords: frequency of homeroom interaction; quality of homeroom interaction; homeroomengagement levelAbstrak: Frekuensi interaksi antara wali kelas dengan siswa dan orang tua/wali murid serta tingkat keterlibatan wali kelas dalam mengatasi permasalahan siswa dan memberikan solusi yang tepat merupakan faktor penting dalam manajemen peserta didik di sekolah. Hasil literature review menunjukkan bahwa interaksi yang sering dan positif antara wali kelas dengan siswa dan orang tua/wali murid dapat meningkatkan motivasi belajar, partisipasi orang tua dalam pendidikan, dan mengurangi perilaku menyimpang. Namun, interaksi yang terlalu sering dan berlebihan dapat memiliki efek yang berlawanan, seperti mengurangi kepercayaan diri siswa dan meningkatkan kecemasan. Wali kelas juga memiliki peran penting dalam mengatasi masalah siswa dan memberikan solusi yang tepat untuk mengatasi berbagai masalah siswa. Namun, tingkat keterlibatan wali kelas dapat bervariasi tergantung pada faktor-faktor seperti pengalaman, motivasi, dan kemampuan. Oleh karena itu, dukungan dan pelatihan diperlukan bagi wali kelas untuk meningkatkan keterampilan dan keterlibatan mereka dalam membantu siswa mengatasi masalah dan mencapai hasil yang lebih baik. Penting untuk menemukan keseimbangan yang tepat dalam frekuensi interaksi dan memastikan bahwa interaksi tersebut berkualitas baik dan positif untuk mendukung pencapaian tujuan belajar siswa.Kata kunci: frekuensi interaksi wali kelas; kualitas interaksi wali kelas; tingkat keterlibatan wali kelas